How Javanese Culture Shaping Political Ideology (Case Study of the People in Yogyakarta) - Nofrima, Sanny; Sudiar, Sonny; Purnomo, Eko Priyo (Jurnal Ilmiah Peuradeun, 2021)
The original Javanese culture of the communities in Java has been running for decades, meaning that this culture has been very rich in elements of universal culture such as the system of social organization, knowledge, arts, religion, and language. Ngayogyakarta Hadiningrat Palace plays an essential role as the center and cultural resource owned by the city of Yogyakarta; one of the areas that are still famous for its cultural guardians, traditions, and behaviors of an ancestor. This research used qualitative methods to obtain data through literature reviews and interviews. Literature review and interview results then became analytical material and adapted to the existing frame of thought as a result of the library studies conducted at the beginning. Then after the analysis process was completed, the results were obtained. This research revealed that the Javanese culture in the people of Yogyakarta affected the political ideology because when speaking about Javanese culture, three aspects cannot be separated in the Javanese community, especially Yogyakarta, Javanese culture, Belief, and religion. A contest will always be syncretism, cannot be constantly intact on assimilation, and acculturation is even alienated (to be drawn). As long as the Javanese people still exist, the Javanese culture will remain alive and develop when the relics of letters, dialectics, and cultures still exist.